Effects of Foliar Boron Treatments on Yield and Yield Components of Fenugreek (Trigonella foenum graecum L.): Detection by PCA Analysis. Issue 16 (8th September 2019) - Beyzi, Erman; Güneş, Adem; Arslan, Mehmet; Şatana, Aziz
ABSTRACT: In this study, effects of foliar boron treatments on yield and yield components of fenugreek plants were assessed with the aid of principal component analysis (PCA) analysis. Experiments were conducted over the experimental fields of Erciyes University Agricultural Research and Implementation Center during the summer growing seasons of the years 2017 and 2018. Gürarslan fenugreek variety was used as the plant material of the experiments. Four different foliar boron (H3 BO3 ) doses (control, 100, 200, 400, and 800 mg lt −1 ) were applied to fenugreek plants. Plant height, number of branches per plant, number of pods per plant, number of seeds per pod, pod length, the first pod height, thousand-seed weight, biological yield, seed yield, and harvest index were measured. Variance analysis revealed that only the seed yield of 2017 was significant ( p < .05) and the other parameters were not found to be significant ( p > .05). PCA analysis was performed to classify and characterize boron doses based on yield and yield components of fenugreek plants. PC1 and PC2 explained about 82% in total variation in 2017 and about 83% in 2018. In both years of the experiments, the greatest biological and seed yields were obtained from 800 mg lt −1 boron treatments. Therefore, 800 mg B lt −1 was recommended to get high seed yield from fenugreek plants.